Treatment of Cystic Craniopharyngioma by Endocavitary Instillation of Yttrium90 Radioisotope—Still a Valuable Treatment Option - Vanhauwaert, Dimitri; Hallaert, Giorgio; Baert, Edward; Van Roost, Dirk; Okito, Jean-Pierre Kalala; Caemaert, Jacques (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Craniopharyngiomas are a challenging pathology in neurosurgery because of their anatomic localization in the (supra)sellar region and their contact with diencephalic structures around the third ventricle. Among the different treatment modalities, stereotactic intracavitary treatment by instillation of yttrium90 radioisotope is a minimally invasive technique of particular use in the treatment of cystic or partially cystic craniopharyngiomas. It can be performed under local anesthesia during a short hospitalization and has a long-lasting effect. This treatment can be repeated or used in combination with other treatment modalities such as microsurgery, endoscopy, conformal external radiation therapy, or stereotactic radiosurgery. Thus, this old and perhaps almost forgotten treatment option is still valuable in the treatment of cystic craniopharyngiomas.
Keywords: craniopharyngioma; yttrium; cystic